2022
DOI: 10.5489/cuaj.7690
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparity on editorial boards of major urology journals

Abstract: Not applicable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…[8] The top 10% of pulmonologists received 83.7% of all general payments between 2013 and 2021. [3] As shown in previous studies, the healthcare industry made the large amounts of general payments to the small fraction of physicians who are in leading positions such as clinical guideline authors, [7,32,[35][36][37] journal editors, [32,[37][38][39][40] society board members, [32,41] and principal investigators of industry-sponsored clinical trials. [28,42] These influential physicians are called key opinion leaders.…”
Section: Discussionmentioning
confidence: 89%
“…[8] The top 10% of pulmonologists received 83.7% of all general payments between 2013 and 2021. [3] As shown in previous studies, the healthcare industry made the large amounts of general payments to the small fraction of physicians who are in leading positions such as clinical guideline authors, [7,32,[35][36][37] journal editors, [32,[37][38][39][40] society board members, [32,41] and principal investigators of industry-sponsored clinical trials. [28,42] These influential physicians are called key opinion leaders.…”
Section: Discussionmentioning
confidence: 89%
“…1 Gender diversity is becoming an increasingly important matter in the medical field. Indeed, there is a growing body of literature showing that females are underrepresented in urology leadership positions such as in senior academic positions 2 , editorial boards 3 and society conferences 4 . However, there are few studies that examine gender equity in medical associations.…”
Section: Introductionmentioning
confidence: 99%
“…As just 1 example, a recently published review of gender disparity on editorial boards of major urology journals shows that only about 12% of editors in 2020 were women. 4 The authors identified some encouraging trends since 2015 so that at least currently these rates approximate the percent of U.S. women urologists. However, a much higher representation, of all equity deserving groups, in academic leadership positions such as editorial boards is required to fortify efforts in bridging the current diversity gaps of our specialty.…”
mentioning
confidence: 99%